2019
DOI: 10.1002/jcp.28211
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma promotes the regeneration of cartilage engineered by mesenchymal stem cells and collagen hydrogel via the TGF‐β/SMAD signaling pathway

Abstract: The tissue engineering technique using mesenchymal stem cells (MSCs) and scaffolds is promising. Transforming growth factor‐β1 (TGF‐β1) is generally accepted as an chondrogenic agent, but immunorejection and unexpected side effects, such as tumorigenesis and heterogeneity, limit its clinical application. Autogenous platelet‐rich plasma (PRP), marked by low immunogenicity, easy accessibility, and low‐cost, may be favorable for cartilage regeneration. In our study, the effect of PRP on engineered cartilage const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…For instance, PRP can stimulate dermal fibroblast migration and proliferation, showing its potential in wound treatment and skin rejuvenation [15]. Therefore, the incorporation of PRP in scaffolds is an advantageous approach, because it represents a simple, efficient and cost-effective method, allowing the immobilization of a number of highly-concentrated bioactive factors, creating an optimized micro-environment, and impacting upon tissue regeneration [10,16,17,18,19]. Various approaches have been developed to immobilize growth factors inside the scaffolds, and these may be envisioned for immobilizing PRP, such as physical encapsulation, absorption onto the biomaterial surface, layer-by-layer self-assembly, covalent conjunctions and extracellular matrix-based binding approaches [20].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PRP can stimulate dermal fibroblast migration and proliferation, showing its potential in wound treatment and skin rejuvenation [15]. Therefore, the incorporation of PRP in scaffolds is an advantageous approach, because it represents a simple, efficient and cost-effective method, allowing the immobilization of a number of highly-concentrated bioactive factors, creating an optimized micro-environment, and impacting upon tissue regeneration [10,16,17,18,19]. Various approaches have been developed to immobilize growth factors inside the scaffolds, and these may be envisioned for immobilizing PRP, such as physical encapsulation, absorption onto the biomaterial surface, layer-by-layer self-assembly, covalent conjunctions and extracellular matrix-based binding approaches [20].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 enhances cartilage cell proliferation and extracellular matrix synthesis [24]. It also contributes to the chondrogenic differentiation of mesenchymal stem cells in vitro [23,28]. TGF-β1 promotes the proliferation of tendon fibroblasts and their synthesis of extracellular matrix, in particular collagen type I, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies showed that PRP could be used as a potent and reliable chondrogenic inducer as a substitute for TGF-β1. Some of its properties, such as its low immunogenicity, easy accessibility and role as an activator of the mechanism of hyaline cartilage production (related with the TGF-β1/SMAD signaling pathway) de ne the PRP as a potentially attractive coadjuvant [35,36]. Reporting a clinical study with 18 patients, Bastos et al concluded that the use of PRP as co-adjuvant together with 40 million BM-MSCs did not provide additional bene ts over the use of BM-MSCs alone [37].…”
Section: Discussionmentioning
confidence: 99%